2023
DOI: 10.3390/children10030586
|View full text |Cite
|
Sign up to set email alerts
|

Medication Intake as a Factor for Non-Initiation and Cessation of Breastfeeding: A Prospective Cohort Study in Greece during the COVID-19 Pandemic

Abstract: Pharmacological treatment may become a barrier for a mother’s breastfeeding goals. We aimed to investigate maternal medication intake as a factor for non-initiation and cessation of breastfeeding and the effect of professional counseling on maternal decision-making. Throughout 2020,847 women were recruited from five healthcare institutions. Information was gathered prospectively with an organized questionnaire through interview during hospitalization and through telephone at 1, 3 and 6 months postpartum. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…respiratory infection, pre-eclampsia), breastfeeding, or at any stage of a woman's life.Occasionally, women receive conflicting advice from healthcare professionals that is not based on evidence-based knowledge, leading them to wean unnecessarily (Hanley et al, 2020, Saha et al, 2015. In a recent study regarding the effect of medication use on breastfeeding initiation and discontinuation conducted in Greece, of all women who discontinued breastfeeding due to medication intake (14.4%, n=57/397), 68.4% of them were led to weaning due to incorrect advice from healthcare professionals (obstetricians, paediatricians, physicians of other specializations) (Tigka et al, 2023). Although various sources of information are reliable on the compatibility of medications with breastfeeding (Hale, 2021, Lactmed, 2006, it was reported that the physicians who counseled mothers had not relied on evidence-based knowledge.…”
mentioning
confidence: 99%
“…respiratory infection, pre-eclampsia), breastfeeding, or at any stage of a woman's life.Occasionally, women receive conflicting advice from healthcare professionals that is not based on evidence-based knowledge, leading them to wean unnecessarily (Hanley et al, 2020, Saha et al, 2015. In a recent study regarding the effect of medication use on breastfeeding initiation and discontinuation conducted in Greece, of all women who discontinued breastfeeding due to medication intake (14.4%, n=57/397), 68.4% of them were led to weaning due to incorrect advice from healthcare professionals (obstetricians, paediatricians, physicians of other specializations) (Tigka et al, 2023). Although various sources of information are reliable on the compatibility of medications with breastfeeding (Hale, 2021, Lactmed, 2006, it was reported that the physicians who counseled mothers had not relied on evidence-based knowledge.…”
mentioning
confidence: 99%